Determinants of Health-Related Quality of Life in Mothers of Children With Autism Spectrum Disorder in Bangladesh - Hasan, Md Mahmudul; Shahjahan, Md; Chowdhury, ABM Alauddin; Nawrin, Sanjida; Rahman, Monnuza; Rahman, Md Arifur; Ahmed, Kazi Jonayed; Debnath, Subeer; Marma, Ukraching (Scripta Medica, 2026)
Background/Aim: Autism spectrum disorder (ASD) has a significant impact on the quality of life of children with this disorder as well as their mothers. ASD prevalence in Bangladesh has been estimated to be 0.15-0.8 %, but the health-related quality of life (HRQoL) of mothers having children with ASD has not been studied. This study aimed to estimate the HRQoL of these mothers and the main determinants that affect it. Methods: This study adopted a cross-sectional design using the SF-scale among 160 mothers who were selected through two stage sampling technique (stratified random and purposive sampling) attending at 16 service centres for persons with disabilities from January to June 2023. Results: The mean age of the participants was 32.78 years and they were mostly married (95 %), were Muslims (84.4 %) and only had primary education (29.4 %). The average monthly family income was 17,781 Bangladeshi Taka (BDT). The total HRQoL was significantly low (37.70 ±18.27). The physical component score (40.32 ± 21.36) and the mental component score (35.08 ± 15.17) revealed that there were severe deficits. The findings also suggest that the maternal age, less education, less income, family structure, children age and child-behaviour issues were all significant predictors of poorer HRQoL (p < 0.05). Conclusions: This paper thus concludes that the HRQoL of the mothers of children with ASD in Bangladesh is critically impaired, due to the effect of socio-economic, family and child related factors.